THE DIMENSIONS OF THE ESTRUCTURAL CRISIS OF CAPITAL: THE CASE OF AGRARIAN COUNTER-REFORM OF MARKET IN BRASIL (1995-2017) - Lima, Rodolfo de Souza [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2017)
This paper aims to reflect on the impacts of the structural crisis of capital in the agrarian question, especially its impacts on the debate on agrarian reform in Brazil and its linkage with the World Bank's agrarian counter-reform. During the 1990s neoliberalism began to be implemented, with strong influence from the International Monetary Fund (IMF) and the World Bank (WB), to the peripheral countries of capitalism, especially in Latin America, Africa and Asia. We understand the WB's agrarian counter-reform as a neo-liberal ideological-political policy and an aspect of capital's structural crisis, incapable of tolerating any threat to sociometabolic control. We will analyze its implementation in Brazil and its treatment by the last four governments (1995-2017).
Keywords: Structural crisis of capital; Neoliberalism; World Bank; Agrarian Counter-Reform of World Bank